Dynamic Open Coordination Cage from Nonsymmetrical Imidazole–Pyridine Ditopic Ligands for Turn‐On/Off Anion Binding. (15th November 2019) - Ogata, Daiji; Yuasa, Junpei
Abstract: This work demonstrates a new nonconventional ligand design, imidazole/pyridine‐based nonsymmetrical ditopic ligands (1 and 1 S ), to construct a dynamic open coordination cage from nonsymmetrical building blocks. Upon complex formation with Pd 2+ at a 1:4 molar ratio, 1 and 1 S initially form mononuclear PdL4 complexes (Pd 2+ (1 )4 and Pd 2+ (1 S )4 ) without formation of a cage. The PdL4 complexes undergo a stoichiometrically controlled structural transition to Pd2 L4 open cages ((Pd 2+ )2 (1 )4 and (Pd 2+ )2 (1 S )4 ) capable of anion binding, leading to turn‐on anion binding. The structural transitions between the Pd2 L4 open cage and the PdL4 complex are reversible. Thus, stoichiometric addition (2 equiv) of free 1 S to the (Pd 2+ )2 (1 S )4 open cage holding a guest anion ((Pd 2+ )2 (1 S )4 ⋅G − ) enables the structural transition to the Pd 2+ (1 S )4 complex, which does not have a cage and thus causes the release of the guest anion (Pd 2+ (1 S )4 +G − ). Abstract : Schaltbarkeit : Nicht‐symmetrische ditopische Liganden (L) treiben die Bildung eines dynamischen offenen Pd2 L4 ‐Käfigs an, der in der Lage ist, die Anionenbindung durch stöchiometrisch gesteuerte Strukturübergänge des Wirtkäfigs ein‐ und auszuschalten.